Cognitive complaints in brain tumor patients and their relatives’ perspectives - Gosselt, Isabel K (Neurooncol Pract, 2020)
BACKGROUND: Cognitive deficits have been frequently assessed in brain tumor patients. However, self-reported cognitive complaints have received little attention so far. Cognitive complaints are important as they often interfere with participation in society. In this study, cognitive complaints were systematically assessed in brain tumor patients. As patients’ experiences and relatives’ estimations may vary, the level of agreement was investigated. METHODS: Brain tumor outpatients (n = 47) and relatives (n = 42) completed the inventory Cognitive Complaints—Participation, assessing cognitive complaints across 10 daily life activities and cognitive domains (total, memory, executive, attention). Cognitive complaints scores were compared between patients with different clinical characteristics (tumor type, number of treatments, the absence/presence of epilepsy). Complaints difference scores in patient-relative pairs were calculated to explore the level of agreement using intraclass correlations (ICC). Furthermore, we explored whether the level of agreement was related to (1) the magnitude of cognitive complaints in patient-relative pairs and (2) patients’ cognitive functioning (assessed with the Montreal Cognitive Assessment). RESULTS: Patients and relatives reported most cognitive complaints during work/education (100%) and social contacts (88.1%). Patients with different clinical characteristics reported comparable cognitive complaints scores. Overall, the level of agreement in patient-relative pairs was moderate-good (ICC 0.73-0.86). Although in 24% of the pairs, there was a substantial disagreement. The level of agreement was not related to the magnitude of complaints in patient-relative pairs or patients’ cognitive functioning. CONCLUSION: Both the perspectives of brain tumor patients and their relatives’ on cognitive complaints are important. Clinicians could encourage communication to reach mutual understanding.